2018
DOI: 10.1111/cpr.12520
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic anticancer effect of formosanin C and polyphyllin VII based on caspase‐mediated cleavage of Beclin1 inhibiting autophagy and promoting apoptosis

Abstract: Objectives Drug combination has a promising and potential development prospect in the treatment of various cancers. The objective of this study is to investigate the synergistic mechanisms of polyphyllin VII ( PVII ) and formosanin C ( FC ) in lung cancer. Materials and methods The combination of FC and PVII influenced on the apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The results showed that polyphyllin VII could induce cancer cell apoptosis via regulating caspase protein activation in oral cancer (30). Several recent studies demonstrated that polyphyllin VII could induce the autophagy process in tumor cells (11,30,35). Distant metastasis is the primary cause of cancer-related deaths.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that polyphyllin VII could induce cancer cell apoptosis via regulating caspase protein activation in oral cancer (30). Several recent studies demonstrated that polyphyllin VII could induce the autophagy process in tumor cells (11,30,35). Distant metastasis is the primary cause of cancer-related deaths.…”
Section: Discussionmentioning
confidence: 99%
“…The PPGinduced apoptosis was confirmed through caspase inhibitor (z-VAD-FMK), which inhibits the cell PPG-induced apoptosis in HONE-1 and NPC-039 cells (Chen et al, 2016). Furthermore, the PPVII and formosanin induced apoptosis in NCI-H460 cell via inhibition of Bcl-2 and activation of Bax, caspase-3,9 (Cui & Man, 2019). The summarized form of mitochondrial-dependent pathway is depicted in Figure 2a.…”
Section: Mitochondrial-dependent Pathwaymentioning
confidence: 92%
“…98 Pretreatment with Z-VAD-FMK (caspase inhibitor) on HepaRG cells increases the percentage of viable cells, indicating that PPVI induces cell apoptosis through the mitochondrial pathway and the Fas deathdependent pathway. 63 PPVII or PPG induces apoptosis in a dose-dependent manner in human NPC, 66 A549, 98 NCI-H1299, 98 HepG-2, 64 SAS, 91 and OECM-1 92 cells by upregulating the expression of DR3, 98 DR5, 98 Fas, 98 caspase-8, 64,66,91 cleaved PARP, 98 and cleaved caspase-3 64,66,91,98 but downregulating the expression of DcR3. 98 The summarized form of the extrinsic apoptotic pathway is depicted in Figure 1B.…”
Section: Extrinsic Apoptotic Pathwaymentioning
confidence: 99%
“… 66 Formosanin C and PPVII increase apoptosis in NCI‐H460 cells by downregulating Bcl-2 and upregulating Bax, caspase-3, −8, and 9. 92 The summarized form of the mitochondrial-dependent pathway is depicted in Figure 1A .…”
Section: Mechanistic Studies Of Pps In Different Cancersmentioning
confidence: 99%
See 1 more Smart Citation